Radiographic and Computed Tomography Correlation of Kienböck's Disease: Is There a Need to Revisit Staging with Improved Imaging? - Mohan, Arvind; Knight, Richard; Ismail, Hiba; Trail, Ian A. (Journal of Wrist Surgery, 2020)
Carpal height ratio and ulnar variance on plain X-ray were measured and compared to the width/height ratio of the lunate as measured on a computed tomography (CT) scan in 50 patients with Kienböck's disease. Width/height ratio of the lunate was also measured in a series of 50 controls. No correlation between ulnar variance and fractures was found. Conversely, the correlation between carpal height ratio on X-ray and width/height ratio on a CT scan was statistically significant. Similarly, the correlation between ulnar variance and width/height ratio was statistically significant. We have concluded that width/height ratio while correlating with carpal height is a better measure of lunate collapse. It also appeared that lunate collapse precedes carpal collapse, specifically most if not all lunates have collapsed prior to reduction in carpal height ratio. Finally, while we are unable to conclude the level at which the width/height ratio of lunate becomes unreconstructable, it does appear that in all Litchman stage 3b and most if not all of 3a the shape of the lunate has altered significantly.
Keywords: Kienböck's disease; radiographic; correlation